Managing Material Cost in Construction Projects (International Journal of Innovative Research in Engineering & Management, 2022)
In the development of project budget cost  estimation of construction material is considered one of the  fundamental important functions. To mollify the risk of  material price volatility, material hedging concept is  another idea reducing unpredictability. This research  coordinated application of fuel hedging with hedging of  material used by carrier like airlines. Utilization of weather  hedging as a point of reference for construction material  supporting application of hedging in the industry of  construction. A guidance is provided by this thesis to apply  material hedging with data and numbers from the practical  use. In addition to this, this postulation coordinated the  model introduced by Macdonald (2013) with this research  model and gave a detail which is of less level in detail to  help real execution of hedging material. In order to look  into the feasibility of hedging material application more  work, research and investigation needed to be carried out.  Feasibility of material hedging and its application can be  known by carrying out investigation in this area.  Investigation of reliability and validity of this thesis model,  in order for its application should be carried out so that  appropriate facts can be put forth and used.
Keywords: Cost Estimation; Gross Domestic Product; Engineering News Record; Engineering and Construction; Hedging Sources